Relationship between social media usage and mental health among members of Kuala Lumpur Golf and Country Club / Aql Alasri and Rozita Abdul Latif - Alasri, Aql; Abdul Latif, Rozita (2024)
This study aimed to investigate the Relationship Between Social Media Usage and Mental Health Among Members of Kuala Lumpur Golf and Country Club. A quantitative research design was applied which was a survey method by distributing a questionnaire via Google form to 421 members of Kuala Lumpur Golf and Country Club. Bergen Social Media Addiction Scale (BSMAS) was used to evaluate social media usage among the members with 6 items. The Depression, Anxiety, and Stress Scale-21 (DASS-21) were used to assess mental health with 21 items. Descriptive analyses were used to determine the members’ highest mental health factors involvement. The result showed no significant difference (p = 0.408) regarding mental health factors between genders. Therefore, it failed to reject the null hypothesis. In addition, there was a significant relationship (p < 0.001) between social media usage and mental health with a moderate positive level of correlation (r = 0.494). The study’s findings will provide a greater understanding of the differences between genders regarding mental health factors among the members of KLGCC. The study found a positive association between social media usage and mental well-being. Social media facilitated stronger connections, fostered community, and served as a channel for sharing golf-related information. The context-specific nature of the relationship, centered around shared interests, aligned with recent research on the benefits of active, engaged social media use in specific communities. To build on the findings, KLGCC should implement workshops, online forums, and campaigns on responsible social media use and mental health awareness. They could also create dedicated social media groups for members to connect over common interests. Regular monitoring and feedback from members could optimize these initiatives for promoting good mental health.